Shear failure characterization in masonry components made with different mortars based on combined NDT methods. (30th September 2019) - Livitsanos, G.; Shetty, N.; Verstrynge, E.; Wevers, M.; Van Hemelrijck, D.; Aggelis, D.G.
Highlights: AE fracture mode characterization of masonry constituents. Successful correlation between full-field strain pattern from DIC with AE indices in masonry components. Shear fracture mode characterization. FEM numerical simulation. Abstract: In this paper, an experimental study conducted on Red Clay brick masonry "triplets" built with Cement and Lime-based mortars is presented. Monitoring of fracture is executed by Acoustic Emission (AE) and Digital Image Correlation (DIC). First, for a profound understanding of individual properties, small scale experiments were conducted for characterization of AE signatures of mortar and brick separately. Representative masonry triplet elements are tested in shear for investigation of the fracture mechanisms in relation to the properties of different mortars. Localization of the cracks as well as source identification is performed by means of AE parameter-based analysis. Their correlation with DIC, accurately showed the location of macro cracking and the developing of strain concentrations even before fracture. This is one of the first investigations where full field strain pattern from DIC are successfully correlated with AE indices in masonry. Numerical simulations were also performed for validation and prediction purposes.